Characterization of physical properties of binary system of erythromycin stearate-sodium starch glycolate by compression force effect - Setyawan, Dwi; Sumirtapura, Yeyet C; Soewandh, Sundani N; Tj, Daryono Hadi (Indonesian Journal of Pharmacy, 2011)
Characterizations  of  the  physical  properties  of  binary  system  of erythromycin stearate (ERS)-sodium starch glycolate(SSG) due to compression force, had been carried out. The solid state properties were evaluated by powder X-ray  diffraction  (PXRD),  scanning  electron  microscope  (SEM)  and  differential thermal  analysis  (DTA)  methods.  The  weight  fraction of  mixtures  ERS:  SSG (90:10),  (80:20)  and  (70:30)  were  compressed  using  hydraulic  press  and  flat plain  punches  with  a  diameter  of  13  mm.  The  compression  force  was  29.5  kN. Diffraction  peaks  at  2θ =  5.6;  10,6  and  25.6°  were  used  to  determine  the  full width at  half  maximum  (FWHM),  crystallite  size  and preferred orientation. Peak broadening  was  calculated  by  measuring  the  FWHM.  FWHM  values,  crystallite size  and  preferred  orientation  of  the  crystallites  were  calculated  by  WinPlotr program. The results of the  study showed that the FWHM value increased at all the crystal lattice as the fraction of SSG increased. The crystallite size and peak intensity  decreased  gradually  as  fraction  of  SSG  increased.  Scanning  Electron Microscope  (SEM)  analysis  indicated  that  SSG  was  dispersed  on  surface  and inside  of  the  tablet  of  ERS  at  all  combination.  The phase  diagram  of  binary system ERS and SSG showed a no interaction of ERS and SSG.Key words : characterization, physical properties, ERS, SSG, compression force